Professional development for cultural diversity: the challenges of teacher learning in context - Szelei, Nikolett (2020)
This article describes context-based professional development (PD) for cultural diversity in a Portuguese school cluster, and discusses how it supports change for justice and equity. Teachers felt the importance of PD and showed willingness and interest to learn. Several teacher learning opportunities were mapped out such as formal workshops, starting small collaborations and teachers’ self-directed informal learning activities. Yet, a rather fragmented character of PD seemed to emerge in terms of content on cultural diversity and forms of learning. Conflicting agendas, scattered teacher collaboration and commitment, and little student and community involvement in planned PD were found. Furthermore, there seemed to be tensions between current PD and teachers’ needs and circumstances; teachers wished for more specific information and pedagogical solutions, more collaboration and more organisational support in PD. Applying a critical multicultural perspective, it is discussed that although the current constellation of PD is a potential start, it might still contribute to teachers’ conceptual confusion and pedagogical insecurities on the field of cultural diversity. It is suggested that criticality towards PD frames is needed to re-centre cultural diversity on the premises of justice, as well as teacher support, and conscious learning with and from students, families and communities.